Summer habitat selection and impacts of human disturbance on leopard cats (Prionailurus bengalensis). Issue 1 (16th December 2020) - Wu, Jiayi; Wang, Jing; Zhu, Yinjiu; Bu, Xiangli; Xiang, Rongwei; Lu, Qingbin; Cui, Shaopeng; Hao, Yinghong; Sheng, Yan; Meng, Xiuxiang
ABSTRACT: Introduction: As a consequence of habitat loss and degradation, the leopard cat ( Prionailurus bengalensis ) in China has become endangered and in need of urgent protection. In situ conservation of leopard cats must be based on an understanding of their habitat selection patterns. We studied the summer habitat of leopard cats using line-transect surveys in the northern Taihang Mountain region surrounding Beijing, China. We compared used plots with non-used plots in elevation, tree canopy, and 20 other ecological variables, and used Vanderploeg＆Scavia's resource selection index (VSI) to analyze habitat preferences. Outcomes/others: Results show that tree canopy, tree height, tree density, and stump quantity of used plots were significantly lower than non-used plots in summer, and that leopard cats preferred habitats located on northern, flat slopes with lower slope, shrub-dominated, dry soil, and less fallen-wood. Leopard cats had a strong tendency to use habitats near human disturbance areas with moderate levels of disturbance intensity. Conclusion: The results suggest that future conservation efforts should emphasize: (1) strengthening the protection and management of forest fringe shrub habitats to improve summer habitat suitability, and (2) environmental education and animal protection campaigns to promote community biodiversity conservation.